Pengaruh Model Quantum Teaching Dengan Menggunakan Media Papan Multifungsi Terhadap Hasil Belajar Matematika Siswa Kelas V UPTD SD Negeri 122366 Pematangsiantar (Jurnal Sekolah Dasar, 2025)
This study aims to see whether there is an influence of quantum teaching using multifunctional board media on the mathematics learning outcomes of fifth-grade students at UPTD SD Negeri 122366 Pematangsiantar. This research is of a quantitative type with a one-group pretest-posttest design. This research was conducted at UPTD SD Negeri 122366 Pematangsiantar. The sampling technique chosen by the researcher is non-probability sampling. This method does not use a fixed or standard selection process, which means that not all members of the population have the same opportunity to be included in the sample. The sample in this study consists of all fifth-grade students of UPTD SD Negeri 122366 Pematangsiantar, totaling 17 students. The questions were first tested at the private elementary school GKPS No.1 on Jln. Sisingamangraja Pematangsiantar. After the trial, it was found that out of the 25 questions tested, 5 were invalid and 20 were valid. This valid question will be used during the research at UPTD SD Negeri 122366 Pematangsiantar. The population of this study consists of all students at UPTD SD Negeri 122366 Pematangsiantar. Research data shows that the influence of quantum teaching using multifunctional board media on mathematics learning outcomes has a pretest average score of 64.41, while the posttest average score is 72.35. This indicates that there is an influence of quantum teaching using multifunctional board media on the mathematics learning outcomes of fifth-grade students. The analysis test used is the t-test value. Based on the research results, t_count = 28.080 with a significance level (2-tailed) of 0.000, a significant probability < 0.05, t_count > t_table = 28.080 with a significance level < 0.05, t_count > t_table = 28.080 > 2.110, thus Ho is rejected and Ha is accepted. This explanation shows that there is an influence of the quantum teaching model using multifunctional boards on the mathematics learning outcomes of fifth-grade students at UPTD SD Negeri 122366 pematangsiantar.